Role of interstitial pinning in the dynamical phases of vortices in superconducting films - Simões, R. P. [UNESP]; Venegas, Pablo Antonio [UNESP]; Mello, Denise Fernandes de [UNESP] (Springer Nature, 2013)
We analyze the vortex dynamics in superconducting thin films with a periodic array of pinning centers. In particular, we study the effect of anisotropy for a Kagomé pinning network when longitudinal and transverse transport currents are applied. By solving the equations of motion for the vortex array numerically at zero temperature, we find different phases for the vortex dynamics, depending on the pinning and driving force. An unusual sequence of peaks for driving force along and perpendicular to the main lattice axes is observed for the differential resistance, reflecting the anisotropy of the transport properties and the complex behavior of the vortex system. This behavior may be understood in terms of interstitial pinning vacancies, which create channels of vortices with different pinning strengths. © 2012 Springer Science+Business Media, LLC.
Keywords: Differential resistance; Periodic pinning; Superconductivity; Vortex dynamics; Differential resistances; Dynamical phasis; Periodic arrays; Pinning strength; Transport currents; Zero temperatures; Anisotropy; Complex networks; Equations of motion; Transport properties; Vortex flow